2015
DOI: 10.20286/ijtmgh-0304128
|View full text |Cite
|
Sign up to set email alerts
|

Travel Guidance for People with Diabetes

Abstract: Diabetes is a disease which occurs by lack of insulin production or its inappropriate function. Patients with diabetes who take insulin suffer from high blood sugar and face unique challenges while travelling as their schedules for insulin dosage and blood sugar regulation change. Therefore they need to organize carefully how they have to travel, instruments they should take, the actions they must accomplish and vigilances they have to regard. Patients with diabetes have to prepare a list consisting of the typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…This study also reported that 3 patients experienced fever which disrupted their blood sugar and 5 patients had to change their insulin dose as they were not accustomed to tropical conditions (Driessen, et al, 1999). A literature review from Morteza et al (2015) stated that the regulation of blood sugar level during travel needed special attention and planning before the travel itself (Morteza, Met al, 2015). A study by Han and Flaherty (2015) showed that there were 30 patients (1.1%) who traveled with Diabetes Mellitus comorbid and under medication (Han & Flaherty, 2015).…”
Section: The Diagnosis Of International Touristsmentioning
confidence: 86%
“…This study also reported that 3 patients experienced fever which disrupted their blood sugar and 5 patients had to change their insulin dose as they were not accustomed to tropical conditions (Driessen, et al, 1999). A literature review from Morteza et al (2015) stated that the regulation of blood sugar level during travel needed special attention and planning before the travel itself (Morteza, Met al, 2015). A study by Han and Flaherty (2015) showed that there were 30 patients (1.1%) who traveled with Diabetes Mellitus comorbid and under medication (Han & Flaherty, 2015).…”
Section: The Diagnosis Of International Touristsmentioning
confidence: 86%
“…The self-administered questionnaire was developed by the principal investigator based on the study objectives and after a literature review of similar studies [8][9][10]. A panel of two diabetologists and one family physician, all of whom provide clinical care for patients with diabetes and are familiar with diabetes guidelines and the survey's development, assessed the questionnaire for appropriateness, accuracy, and relevance and were asked to critique the questionnaire's content.…”
Section: Participants and Survey Instrumentmentioning
confidence: 99%
“…The self-administered questionnaire was developed by the principal investigator (RD) based on the study objectives and after a literature review of similar studies. [8][9][10] A panel of two diabetologists and one family physician, all of whom provide clinical care for patients with diabetes and are familiar with diabetes guidelines and the survey's development, assessed the questionnaire for appropriateness, accuracy, and relevance and were asked to critique the questionnaire's content. To ensure the face validity of the questionnaire, it was presented to a sample of 20 participants in a pilot study and then finalized.…”
Section: Participants and Survey Instrumentmentioning
confidence: 99%